Advancing Multicultural Dialogues in Education (Springer International Publishing, 2018)
This edited collection advances the call for continued multicultural dialogues within education. Dialogue and education are the two most essential tools that can help tackle some of the biggest problems we are facing across the globe, including fanaticism, chauvinistic nationalism, religious fundamentalism and racism. The contributors to this book explore the necessity of sustained dialogue within the wider social and political sciences alongside in national and international politics, where more multicultural voices need to be heard in order to make progress. The book builds on existing evidence and literature to advocate in favour of this movement, and highlights how important and significant multiculturalism and multicultural education remains. It will be essential reading for students and academics working in the fields of education and sociology, particularly those with an interest in social justice and multiculturalism.